Adsorption Characteristics and Transport Behavior of Cr(VI) in Shallow Aquifers Surrounding a Chromium Ore Processing Residue (COPR) Dumpsite - Yu Liu; Yin Li; Yucheng Hu; Khan M. G. Mostofa; Siliang Li; Zhenying Liu (Journal of Chemistry)
This study explored the stratigraphic distribution and soil/shallow aquifer characteristics surrounding a chromium ore processing residue (COPR) dumpsite at a former chemical factory in China. Total Cr levels in top soils (5–10 cm) nearby the COPR dumpsite were in the range of 8571.4–10711.4 mg/kg. Shallow aquifers (1–6 m) nearby the COPR dumpsite showed a maximum total Cr level of 9756.7 mg/kg. The concentrations of Cr(VI) in groundwater nearby the COPR dumpsite were 766.9–1347.5 mg/L. These results display that the top soils, shallow aquifers, and groundwater of the study site are severely polluted by Cr(VI). Then, three aquifers (silt, clay, and silty clay), respectively, collected from the depth of 1.4–2.4 m, 2.4–4.8 m, and 4.8–11.00 m were first used to evaluate the adsorption characteristics and transport behavior of Cr(VI) in shallow aquifers by both batch and column experiments. The adsorption of Cr(VI) on tested aquifers was well described by pseudo-second-order equation and Freundlich model. The adsorption capacities of Cr(VI) on three aquifers followed the order: clay > silty clay > silt. The kinetics proved that Cr(VI) is not easily adsorbed by the aquifer mediums but transports with groundwater. Thermodynamics indicated that Cr(VI) adsorption on tested aquifers was feasible, spontaneous, and endothermic. Cr(VI) adsorption on tested aquifers decreased with increasing pH. Furthermore, the transport of Cr(VI) in adsorption columns followed the sequence of clay < silty clay < silt. Desorption column experiments infer that the Cr(VI) adsorbed on aquifers will desorb and release into groundwater in the case of rainwater leaching. Therefore, a proper treatment of the COPR and a comprehensive management of soils are vital to prevent groundwater pollution.